Analysis of Trust and Quality of Service on Patient Satisfaction at Barito Selatan Hospital in Central Kalimantan - Aryawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research in the field of services marketing aims to determine and analyze the influence of service quality dimensions of tangible, reliability, responsiveness, assurance and empathy partially and simultaneously on patient satisfaction at the South Barito Regency hospital in Central Kalimantan Province. The research method used in this research is a quantitative method with the type of research, namely field research and analyzed using partial study statistics (PLS). The sample in this research was selected using non-probability sampling techniques. The number of samples used was 200 patients as respondents. The results of this research show that: tangible service quality has a significant effect on the patient satisfaction variable, the service quality dimension of reliability has a significant effect on the patient satisfaction variable, the service quality dimension of responsiveness has a significant effect on the patient satisfaction variable, the service quality dimension of assurance has a significant effect on the variable patient satisfaction, the service quality dimension of empathy has a significant effect on the patient satisfaction variable